Aerial Exploration - W. G. Jewitt (Canadian Institute of Mining, Metallurgy and Petroleum, 1931)
Introduction The use of the aeroplane in prospecting is already familiar to everyone connected with the mining industry. Apart from transportation companies, three organizations, the N. A. M. E., the Dominion Explorers, and the Exploration Department of the Consolidated Mining and Smelting Company, have made the aeroplane an everyday feature in every mining district in Canada. Its use has been demonstrated successfully in the mountains of British Columbia, but perhaps its greatest field lies in the Canadian Shield, where the numerous lakes and rivers afford an almost continuous series of landing places for aeroplanes, on floats in the summer and on skis in the winter. To the man who has travelled by canoe, toiling over fly-infested portages or held for days at a time, wind-bound, on the big lakes, the ease, speed, and cheapness of aeroplane travel have marked the beginning of a new era, in which ground previously covered with difficulty in a month or more is travelled with ease in a few hours. Development of an air service in the Consolidated Mining and Smelting Company has proceeded on different lines from those of other organizations, and this paper is concerned with that development.